Impact of sustainable development indicators on economic growth: Baltic countries in the context of developed Europe - Lapinskienė, Giedrė; Peleckis, Kęstutis (Business: Theory and Practice, 2009)
The paper aims to analyse sustainable development indicators taken from the Eurostat database and to determine a rational relationship between the sustainable development indicators and the economic growth of the country. The suggested hypothesis implies that the process of the country’s development differs depending on the stage of the development. In order to establish the relationship between the sustainable development and the economic growth, the correlation analysis was used. Lithuania, Latvia and Estonia were taken as the research objects and the results obtained were compared with those describing the developed countries (Austria, Belgium, Denmark, Netherlands, France, Germany). The results obtained outline the main economic trends as well as determining their variation depending on the development stage of the country.Darnaus vystymosi rodiklių poveikis ekonominiam augimui:  Baltijos šalys išsivysčiusios Europos konteksteSantrauka. Darbo tikslas – atskleisti ekonomiškai pagrįstus ryšius tarp darnaus vystymosi, remiantis Eurostat duomenų baze, ir  šalies  ekonomikos  augimo  rodiklių.  Iškelta  hipotezė –  šalies  išsivystymo  procesas  kinta  priklausomai  nuo  ekonominio išsivystymo lygio. Statistinei rodiklių analizei atlikti taikytas koreliacijos metodas. Tyrimo objektas yra Lietuva, Latvija, Estija, gauti rezultatai lyginami su išsivysčiusiomis valstybėmis (Austrija, Belgija, Danija, Nyderlandų Karalystė, Prancūzija, Vokietija). Gauti rezultatai nusako ekonomines tendencijas ir jų skirtumus skirtingo išsivystymo lygio šalyse.Reikšminiai žodžiai: darnus vystymasis, rodikliai, Lietuva.First published online: 29 May 2009